2018
DOI: 10.21833/ijaas.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and secure unstructured data sharing in multi-cloud storage using the hybrid crypto-system

Abstract: The aim of the paper is to offer an architectural framework to help in securing data sharing processes in the multi-cloud storage. For example, the paper highlights the ways of achieving a secure data sharing through the application of the cryptographic index-based data slicing techniques. It seeks to prevent malicious insider through data encryption using 3DES in every part of the file and RSA for the encryption of private key. In addition this work also enhances the privacy of secure data sharing using dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Future enhancements have been suggested that implement dynamic data slicing using 3DES. 19,20 It supports the use of highly dispersed computing and storage elements in the form of FOG. Multicloud FOG has been considered as a hybrid architecture working together in an integrated fashion, providing highly dispersed facilities.…”
Section: Related Workmentioning
confidence: 99%
“…Future enhancements have been suggested that implement dynamic data slicing using 3DES. 19,20 It supports the use of highly dispersed computing and storage elements in the form of FOG. Multicloud FOG has been considered as a hybrid architecture working together in an integrated fashion, providing highly dispersed facilities.…”
Section: Related Workmentioning
confidence: 99%
“…e given framework is found based on 3DES and RSA encryption. On the contrary, this methodology is lacking in efficiency, privacy, and overload middleware through multiple functions [26]. In this paper, the authors studied, multilevel licensing framework approval preservation cloud penetrating data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [9] the author uses a hybrid method such as Advanced ndard (AES), Rivest Shamir Adleman (RSA), Blowfish to secure data. Fully Homomorphic E) is utilized to encrypt data and then encrypted data is distributed over multi-cloud [10]. In [6] to S is used in combination with MD5.…”
Section: Figure 1: Cloud Overviewmentioning
confidence: 99%
“…Fully Homomorphic Encryption (FHE) is utilized to encrypt data and then encrypted data is distributed over multicloud [9]. In [5] to secure data, AES is used in combination with MD5, however, there is a possibility of a cache-based timing attack on AES [10]. There are chances of Biclique attacks on AES, as proved in [11].…”
Section: Figure 1: Cloud Overviewmentioning
confidence: 99%
See 1 more Smart Citation